Body Composition in Acromegaly According to Disease Activity – Performance of Dual X-Ray Absorptiometry and Multifrequency Bioelectrical Impedance Analysis - Lopes, Aline Alves; Albuquerque, Luciano; Fontes, Mayara; Rego, Daniella; Bandeira, Francisco (Frontiers in Endocrinology, 2022)
Introduction: the present study aims to evaluate body composition and its relationship with hormonal control in acromegaly, also comparing the performance of Bioelectrical impedance analysis (BIA), a more accessible method, with dual X-ray absorptiometry (DXA), technology frequently used in current studies. Methods: we studied 28 patients (78% female) of whom 13 with active disease, mean age was 52.11 ± 12.53 years; 64% had high blood pressure (HBP) and 50% had type 2 diabetes (T2D). Results: Although patients with controlled disease had lower serum GH (1.2 ± 1.68µg/L vs 6.61 ± 6.40µg/L, p=0.001) and IGF-1 (158.89 ± 54.53ng/mL and 503.31 ± 253.25ng/mL, p<0.001), they did not differ in body composition: percentage of fat mass: 36.13 ± 11.84% vs 37.73 ± 8.76%, p=0.691 for BIA and 37.10 ± 10.21% vs 37.89 ± 7.32%, p=0.819 for DXA; muscle mass parameters, BIA: FFMI 18.68 ± 2.38kg/m² vs 19.14 ± 1.59kg/m², p=0.560; SMI 10.17 ± 1.39kg/m² vs 10.53 ± 1.01kg/m², p=0.438; DXA: Baumgartner 7.99 ± 1.43kg/m² vs 8.02 ± 1.24kg/m², p=0.947, respectively for controlled and active disease. Patients with controlled acromegaly had lower fasting glucose (110.33 ± 55.48mg/dL vs 129.77 ± 40.17mg/dL, p=0.033) and were less likely to have persistent T2D (28.6 vs 71.4%, p=0.008) and HBP (38.9 vs 61.1%, p=0.049). There were strong positive correlations between BIA and DXA for fat mass (r=0.929, p<0.001) and muscle mass parameters: SMI X Baumgartner: r=0.890, p<0.001; and FFMI X Baumgartner: r=0.868, p<0.001. Conclusion: our data showed similar results in body composition assessment by BIA and DXA, with good correlation between the methods, regardless of the hormonal status of acromegaly. Furthermore, in patients with adequate hormonal control, there was preservation of muscle mass and a lower prevalence of metabolic comorbidities, such as T2D and HBP.